# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime } = -3 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+20 y^{\prime }+51 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime }+20 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\beta ^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}5 y^{\prime \prime }+2 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}a y y^{\prime \prime }+b y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+c y^{\prime }+k y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{n} = 0
\] |
✓ |
✓ |
|
\[
{}a y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}a {y^{\prime \prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}a {y^{\prime \prime }}^{n} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }+2 u^{\prime }+u = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+l y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a y^{\prime }+b y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a y^{\prime }+b y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{\prime \prime }-5 x^{\prime }-3 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-2 x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{2}+x^{\prime }+\frac {x}{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-2 x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{2}+x^{\prime }+\frac {x}{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime }+6 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-12 x = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{\prime \prime }+3 x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{2}+\frac {5 x^{\prime }}{6}+\frac {2 x}{9} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\frac {x^{\prime }}{8}+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-2 a x^{\prime }+a^{2} x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-x^{\prime }-6 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-2 x^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime }+12 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-12 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }-14 y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+7 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }+4 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }-6 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+29 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+58 y = 0
\] |
✓ |
✓ |
|